Deciphering Solar Magnetic Activity: The Solar Cycle Clock - Leamon, Robert J.; McIntosh, Scott W.; Title, Alan M. (Frontiers in Astronomy and Space Sciences, 2022)
The Sun's variability is controlled by the progression and interaction of the magnetized systems that form the 22-year magnetic activity cycle (the "Hale Cycle"") as they march from their origin at 55º latitude to the equator, over 19 years. We will discuss the end point of that progression, dubbed "terminator" events, and our means of diagnosing them. In this paper we expand on the Extended Solar Cycle framework to construct a new solar activity "clock" which maps all solar magnetic activity onto a single normalized epoch based on the terminations of Hale Magnetic Cycles. Defining phase 0 * 2pi on this clock as the Terminators, then solar polar field reversals occur at 0.2 * 2pi, and the geomagnetically quiet intervals centered around solar minimum start at 0.6 * 2pi and end at the terminator, thus lasting 40% of the cycle length. At this onset of quiescence, dubbed a "pre-terminator," the Sun shows a radical reduction in active region complexity and, like the terminator events, is associated with the time when the solar radio flux crosses F10.7 = 90 sfu. We use the terminator-based clock to illustrate a range of phenomena that further emphasize the strong interaction of the global-scale magnetic systems of the Hale Cycle: the vast majority, 96%, of all X-flares happen between the Terminator and pre-Terminator. In addition to the X-rays from violent flares, rapid changes in the number of energetic photons—EUV spectral emission from a hot corona and the F10.7 solar radio flux—impinging on the atmosphere are predictable from the Terminator-normalized unit cycle, which has implications for improving the fidelity of atmospheric modelling.